2016
DOI: 10.20307/nps.2016.22.3.209
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis withKigelia africanafruits in HCT116 Human Colon Cancer Cells via MAPKs Signaling Pathway

Abstract: -Kigelia africana (Lam.) Benth. (Bignoniaceae) is a flowering plants in South, Central and West Africa and commonly known as the sausage tree (Eng.); worsboom (Afr.); umVunguta, umFongothi (Zulu); Modukguhlu (North Sotho); Muvevha (Venda). The dried, powdered fruits are used as dressing for wounds and ulcers, haemorrhoids, rheumatism, purgative, skin-firming, lactation in breast-feeding mothers. The aim of this study is to investigate the cytotoxic and apoptotic potentials of 70% ethanolic extracts of Kigelia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Erythrina alkaloids: erythraline, erysodine, erysotrine, 8oxoerythraline, and 11-methoxyerysodine [133] Cytotoxicity with LC 50 value > 240 μg/ml [134]. Seed oil suppressed human colon adenocarcinoma (Caco-2) and human embryonic kidney (HEK-293) cell growth in a dose-dependent manner [140] An 80% methanol extract of the roots exhibited cytotoxicity to brine shrimps with LC 50 of 7.2 μg/ml [138] Fruit extracts increased the sub-G1 phase (apoptosis) population in HCT116 human colon cancer cells [141] Markhamia lutea (Benth.) K. Schum Cycloartane triterpenoids, musambins A-C and their 3-Oxyloside derivatives musambiosides A-C [142], Oleanolic acid, pomolic acid, 2-epi-tormentic acid, musambin A, and b-sitosterol-3-O-b-D-glucopyranoside [143,144] Anticancer activity against Ehrlich ascites carcinoma cells with an IC 50 value of 27.0 μg/mL [143].…”
Section: Anticancer Plants Used In Local Communities Of Ugandamentioning
confidence: 99%
“…Erythrina alkaloids: erythraline, erysodine, erysotrine, 8oxoerythraline, and 11-methoxyerysodine [133] Cytotoxicity with LC 50 value > 240 μg/ml [134]. Seed oil suppressed human colon adenocarcinoma (Caco-2) and human embryonic kidney (HEK-293) cell growth in a dose-dependent manner [140] An 80% methanol extract of the roots exhibited cytotoxicity to brine shrimps with LC 50 of 7.2 μg/ml [138] Fruit extracts increased the sub-G1 phase (apoptosis) population in HCT116 human colon cancer cells [141] Markhamia lutea (Benth.) K. Schum Cycloartane triterpenoids, musambins A-C and their 3-Oxyloside derivatives musambiosides A-C [142], Oleanolic acid, pomolic acid, 2-epi-tormentic acid, musambin A, and b-sitosterol-3-O-b-D-glucopyranoside [143,144] Anticancer activity against Ehrlich ascites carcinoma cells with an IC 50 value of 27.0 μg/mL [143].…”
Section: Anticancer Plants Used In Local Communities Of Ugandamentioning
confidence: 99%
“…These results correlated with the previous study that artonin E showed anti-proliferation and apoptosis induction by induced cleaved caspase-7 and cleaved-PARP activation in A431 skin cancer cells, resulting in apoptosis cell death [ 26 ]. In general, there are two types of caspases, initiator and effector caspase; the caspase cascade, caspase-9 (initiator caspase) can activate caspase-7 (effector caspase), which then cleaves vital substrates, such as PARP that plays an important role in DNA repairing [ 30 ]. These present results related to previous research demonstrating that artonin E induced apoptosis in several cancer cell types including MDA-MB231, MCF-7, SKOV-3, H460, and A431 [ 11 , 15 , 24 , 27 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer is a lethal disease typically caused by mutations that result in uncontrolled cell growth that subsequently invades surrounding tissues; such systemic metastasis is now the second leading cause of death worldwide [1,2]. Natural products from many species (including microorganisms, marine organisms, and other plants) have proved valuable resources for securing molecular treatments for cancer [3][4][5][6][7][8][9][10][11][12]. Indeed, many anti-cancer drugs derived from natural products (such as paclitaxel, doxorubicin, and rapamycin) are currently either in clinical use or preclinical evaluation to treat cancer patients [4,5,13].…”
mentioning
confidence: 99%